La soledad y la vida del maestro - García Hoz, Víctor (Revista Española de Pedagogía, 2019)
The author makes a deep study of solitariness and the emotional responses that this state provokis in man. Solitariness schows two faces a sad one and a glad one. Weariness, spleen and anguish are the expressions of its first aspect. But man has the possibility of drawing good from bad situations. In order to do that, man must be able to speak o things with himself and with God. The schoolmaster in rural areas meets with two kinds of weariness, the personal and the professional one, wich, besides spleen and the fact of being the objetc of the countrymen's continuous watch constitute the negative aspect of his solitariness. But the schoolmaster can also make of solitariness a condition to get a more efficient life. To this end the rural schoolmaster must have a strong personality and be educated for it. Besides he needs the help of those who woork in his same tasks and have his saine duties. The societies of schoolmasters, the regular meetings, the professional magazines and any other way of relationship with other teachers allow the rural schoolmaster to traverse the road that goes from the «ego» to the «nos» which will enable him to have a sense of being backed by those who have devoted their lives to his same task
Keywords: soledad; maestro; Revista Española de Pedagogía